Selected environmental aspects in the context of the concept of CSR in logistics companies - Mateusz Kurowski (Economic and Environmental Studies (E&ES), 2017)
Corporate social responsibility is a complex concept, where ecology is one of the key elements. From the point of view of logistics, care for the environment and respect for non-renewable resources is a particularly important issue. The essence of logistics is the movement of people and cargo, that is possible only by using a certain amount of energy. Companies operating in this sector, by definition cannot, therefore, be neutral with respect to the environment. They can, however, minimize the ecological footprint. In practice, it turns out that the involvement of businesses in this area is varied. The aim of the article is to assess ecological facet of logistics companies' activity and their differentiation in this area according to their specialization. Statistical analysis of selected environmental aspects shows a weak ecological score of logistics companies compared to other industries. What is more, ecological score of logistics businesses is varied between specialization groups. In overall, the leading group of companies is transportation infrastructure which reached the highest average score. The only sector which significantly lags behind the others is road and rail. It turns out that the most problematic ecological aspects for assessed companies are: reduction of hazardous waste and air emissions other than GHG, and environmental requirements in relation to suppliers.
Keywords: O13; L91; L92; L93; 330; corporate social responsibility; CSR; ecology; green logistics; logistics